Retinopathy of prematurity: screening programme for preterm infants in Ondo State, South-West, Nigeria - Adegbehingbe, Stella A.; Oluwafemi, Rosena O. (International Journal of Research in Medical Sciences, 2024)
Background: Retinopathy of prematurity (ROP) is one of the avoidable causes of childhood blindness in the whole world. The disease can be mild, it can resolve spontaneously, and it could also have a grave consequence of blindness. As such, all extreme and very preterm babies at risk for ROP and having additional systemic co-morbidities and risk factors must be screened. Methods: Preterm babies with gestational age up to 32 weeks and birth weight less than 1500 g were prospectively recruited into the study. Retinal examination using binocular indirect ophthalmoscope with +20DS lens was done at 4 to 6 weeks post-delivery and were subsequently followed up. Data were analyzed using the software package for social science (SPSS) version 20.0 Categorized data were presented as percentages, p value <0.05 was considered significant. Results: Fifty-two preterm babies with birth weight ranging between 900-1500 g and gestational age ranging between 26-32 weeks were examined. ROP was detected in 7 babies (13.5%), Four (57.1%) babies had stage 1 ROP, 3 (42.9%) had stage 2 disease and none had stage 3 disease. ROP was commoner in the female babies 6 (86%). Neonatal sepsis and use of up to 3-days supplemental oxygen therapy (p=0.024) were the only risk factors associated with all the babies with ROP in the study. Conclusions: Prevalence of ROP was 13.5% in the current study with risk factors of neonatal sepsis and use of supplemental oxygen of up to 72 hours post-natal life.